2018
DOI: 10.1111/jocn.14555
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the contemporary role of the intellectual disability nurse: A review of the literature

Abstract: Understanding the skills required of nurses caring for people with intellectual disability provides the opportunity for more nurses to develop these specialised relational skills and for this branch of nursing to attract professional recognition that is currently limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 40 publications
(84 reference statements)
0
35
0
Order By: Relevance
“…The results of this study provide support for the idea that nurse intellectual disability specialization may promote more beneficial health outcomes for adults with intellectual disabilities as mediated by nurse behaviour. Jaques et al () found that the skill set of intellectual disability nurses is similar to non‐intellectual disability nurses in terms of physical skills, but differs in relational terms, with intellectual disability nurses demonstrating increased patience and resilience. The results of this study support the assertion that intellectual disability nurses may have a unique attitudinal skill set to care for individuals with disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study provide support for the idea that nurse intellectual disability specialization may promote more beneficial health outcomes for adults with intellectual disabilities as mediated by nurse behaviour. Jaques et al () found that the skill set of intellectual disability nurses is similar to non‐intellectual disability nurses in terms of physical skills, but differs in relational terms, with intellectual disability nurses demonstrating increased patience and resilience. The results of this study support the assertion that intellectual disability nurses may have a unique attitudinal skill set to care for individuals with disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…The dyad and the systems are under pressure from the emergence of the NDIS.A recent literature review focussing on what it is that constitutes the practice of IDD nursing, identified that the IDD nurse role is uniquely relational(Jaques, Lewis, Wiese, O'Reilly, & Wilson, 2018). Here, the nurse/patient dyad is represented in as a "bridge" set between the different pillars of the health and disability systems.…”
mentioning
confidence: 99%
“…A recent literature review focussing on what it is that constitutes the practice of IDD nursing, identified that the IDD nurse role is uniquely relational(Jaques, Lewis, Wiese, O'Reilly, & Wilson, 2018).The IDD nurse is not only unique because of the nursing skills they , but also for the way they relate to their clients. This relational role takes time to develop, requires personal investment and its absence can lead to negative outcomes.…”
mentioning
confidence: 99%
“…In the UK context, Mitchell () previously argued that nurse education over the decades has actually been very responsive to the changing political and policy contexts where the focus of education has shifted from the pre‐1970s sickness model towards the more holistic, community‐based and social model reflecting the current climate. A review of the contemporary literature to explore the specialist role/s and the specialist skills of the ID nurse highlighted that ID nursing in the modern era requires a unique combination of both relational and practical skills (Jaques et al., ). In an Irish study about deinstitutionalisation, families reported feeling that the new breed of nurses were better trained with a focus on the pursuit of excellence and holistic care (Doody, ).…”
Section: Discussionmentioning
confidence: 99%
“…While beyond the scope of this paper, the complexity of the nursing role has been identified by Jaques, Lewis, Wiese, O'Reilly, and Wilson (2018) as not so much a uniquely technical nursing role, but a uniquely relational role due to the limitations in intellectual function and adaptive behaviour. The number of specialist ID nurses currently working in Australia is difficult to identify; however, a total of 107 solely qualified disability nurses from the pregeneric registration era are still registered in 2017 (Nursing & Midwifery Board of Australia, 2017).…”
mentioning
confidence: 99%